1992
DOI: 10.1007/bf00223996
|View full text |Cite
|
Sign up to set email alerts
|

Using the shifted multiplicative model to search for “separability” in crop cultivar trials

Abstract: The shifted multiplicative model (SHMM) is used in an exploratory step-down method for identifying subsets of environments in which genotypic effects are "separable" from environmental effects. Subsets of environments are chosen on the basis of a SHMM analysis of the entire data set. SHMM analyses of the subsets may indicate a need for further subdivision and/or suggest that a different subdivision at the previous stage should be tried. The process continues until SHMM analysis indicates that a SHMM with only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
0
22

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 14 publications
0
125
0
22
Order By: Relevance
“…The GxE interaction was decomposed by the AMMI into two principal components, but only de first axis was significant based on the F R test (Cornelius et al 1992). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GxE interaction was decomposed by the AMMI into two principal components, but only de first axis was significant based on the F R test (Cornelius et al 1992). …”
Section: Resultsmentioning
confidence: 99%
“…In AMMI models, the most appropriate choice in terms of the number of axis to be retained (PCA) and capable of explaining the interaction of the standard portion is determined by the (SQ GE ) ratio, accumulated until the n th axis (Σ n k-1 λ k /SQ GE ). The F R test (Cornelius et al 1992) was used to evaluate the AMMI residue and the choice of the significant PCA axis. A significant result suggests that at least a multiplicative term must still be added to the already adjusted n axis until the best AMMI model is found.…”
Section: Lk Morais Et Almentioning
confidence: 99%
“…É necessário selecionar os genitores exóticos para eliminar os genótipos que tenham alelos responsáveis por fenótipos indesejáveis ligados aos genes de interesse; outra justificativa seria o aumento da freqüência de alelos favoráveis na população, principalmente poligenes que controlam caracteres quantitativos como a produtividade de grãos e, dessa maneira, aumentar a probabilidade de obtenção de linhagens superiores no fim do programa (ROCHA, 2002). De acordo com DUARTE (2001), a análise AMMI representa um dos potenciais instrumentos para que se possa aprofundar na compreensão dos fatores realmente envolvidos na manifestação da interação G x E. Para tanto, o método estima o efeito da interação GxE através da análise multivariada (análise de componentes principais -ACP e decomposição por valores singulares -DVS) para descrever o padrão subjacente aos dados de uma matriz de interação (G x E), fazendo a decomposição da soma de quadrados da interação G x E (SQ GxE ) em eixos ou componentes principais da interação (IPCA), sendo adotado aqui o critério "pos-dictivo" pelos testes F Gollob e F R apresentado por CORNELIUS et al (1992) e PIEPHO (1995), para seleção de modelos AMMI mais preditivos e parcimoniosos.…”
Section: Resultsunclassified
“…O ruído AMMI, reunindo os demais termos da (não retidos no modelo selecionado), também foi testado de maneira a assegurar o seu caráter desprezível (DUARTE e VENCOVSKY, 1999), através da significância do teste FR (CORNELIUS et al, 1992;PIEPHO, 1995):…”
Section: Methodsunclassified
“…For AMMI (Additive Main Effects and Multiplicative Interactions), significance level was set at 5% according to the F r test criterion of Cornelius et al (1992). Some studies have suggested adjustments to the AMMI method like the inclusion of additional genotype (AG), to increase the precision of identifying superior lines (Pacheco et al, 2005).…”
Section: Methodsmentioning
confidence: 99%